INJURIES INCIDENCE IN IRONMAN BRAZIL 2006 PARTICIPATING (Fiep Bulletin - online, 2014)
The Ironman is a triathlon race that consists in 3.8km of swimming, 180km of cycling 42km of running. The number of hours and the volume of training of Ironman athletes may increase the rate of injuries that would cause the interruption of practice and the need of treatment. The aim of this study was to identify the incidence of injuries in Ironman Brazil 2006 athletes, regarding the frequency of occurrence, the injured body region and the diagnosis. The sample was composed by 209 (176 male and 33 female) athletes from different countries. A mixing questionnaire was used as instrument to identify the time of practice and the incidence of injuries (affected body region and diagnosis). 127 subjects (60%) had already suffered some injury related to the modality. In upper limb shoulder was the most affected region (68,7%)Regarding the lower limb (MMII), knee was the most affected region (38,8%) followed by the ankle (17,6%) and foot (16, 4%). In the trunk, lumbar region was the most affected (57,7%). Muscle injury was the most common diagnosis for all of the body segments (56% in upper limbs, 53% in lower limbs and 46% in trunk). Injuries reported by the athletes are usually related to the specific modalities: in swimming, it is higher the incidence of injuries in shoulder; in cycling, the most affected place is the lumbar region; and in running, the knee is the most affected region. By identifying the incidence of injuries, the affected body regions and the diagnosis this study provides subsides to plan Table 3: Injuries’ diagnosis in upper limbs, lower limbs and trunk Diagnosis Upper limbs Lower limbs Trunk Muscle Injury 56% 53% 46% Bone Injury 15% 17% 16% Skin Injury 15% 10% 23% Ligament Injury 14% 20% 14% FIEP BULLETIN Volume 78 - Special Edition - ARTICLE I - 2008 prevention programs in order to decrease the occurrence and recidivism of injuries.
Keywords: Ironman; injury; epidemiology